2017
DOI: 10.1007/s40290-017-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effectiveness of Risk Minimization Measures for Tigecycline in the European Union

Abstract: Background Risk minimization measures (RMM) were implemented from February 2011 in the European Union to address risks of superinfection, off-label use and lack of efficacy associated with tigecycline. The objective of this study was to evaluate RMM effectiveness by describing prescription patterns among adults and children treated with any dose of tigecycline for any indication pre-and post-RMM implementation; incidence proportions of superinfection and lack of efficacy among adults treated with approved dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Of note, risk minimization measures have previously been shown to be effective. They were introduced to reduce the off-label use of tigecycline, and a retrospective study of their effectiveness concluded that this did decrease following implementation [44].…”
Section: What Do the Survey Results Tell Us About Armm Effectiveness?mentioning
confidence: 99%
“…Of note, risk minimization measures have previously been shown to be effective. They were introduced to reduce the off-label use of tigecycline, and a retrospective study of their effectiveness concluded that this did decrease following implementation [44].…”
Section: What Do the Survey Results Tell Us About Armm Effectiveness?mentioning
confidence: 99%
“…The Tigecycline Post-Authorization Safety Study (PASS) was an observational cohort study that employed retrospective chart abstraction study design in which pre-recorded patient-centred data were reviewed (EU registration number EUPAS3674). 14 The study enrolled 777 patients from 13 sites in 5 EU countries (2 sites in Austria, 4 in Germany, 3 in Italy, 2 in Greece, 2 in the UK). The study primary objectives were: 1) to evaluate the effectiveness of risk minimisation measures (RMM) for tigecycline by describing prescription patterns among patients treated with any dose of tigecycline for any indication (on-or off-label) in the EU before and following implementation of RMM, and 2) to determine the incidence of superinfection and lack of efficacy among adult patients treated with approved doses of tigecycline for cIAI and cSSTI in the EU prior to and after implementation of RMM.…”
Section: Safety Datamentioning
confidence: 99%